Regulatory network and interplay of hepatokines, stellakines, myokines and adipokines in nonalcoholic fatty liver diseases and nonalcoholic steatohepatitis - Yang, Bing; Lu, Liqing; Zhou, Dongmei; Fan, Wei; Barbier-Torres, Lucía; Steggerda, Justin; Yang, Heping; Yang, Xi (Frontiers in Endocrinology, 2022)
Fatty liver disease is a spectrum of liver pathologies ranging from simple hepatic steatosis to non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), and culminating with development of cirrhosis or hepatocellular carcinoma (HCC). The pathogenesis of NAFLD is complex and diverse, and there is a lack of effective treatment measures. In this review, we address hepatokines identified in the pathogenesis of NAFLD and NASH, including the signaling of FXR/RXR, PPARα/RXRα, adipogenesis, hepatic stellate cell activation/liver fibrosis, AMPK/NF-κB, and type 2 diabetes. We also highlight the interaction between hepatokines and cytokines or peptides secreted from muscle (myokines), adipose tissue (adipokines) and hepatic stellate cells (stellakines) in response to certain nutritional and physical activity. Cytokines exert autocrine, paracrine, or endocrine effects on the pathogenesis of NAFLD and NASH. Characterizing signaling pathways and crosstalk amongst muscle, adipose tissue, hepatic stellate cells and other liver cells will enhance our understanding of interorgan communication and potentially serve to accelerate the development of treatments for NAFLD and NASH.